Enhanced MMSE-FDE method for TS-OFDM under higher mobile environments - Pongsathorn Reangsuntea; Pisit Boonsrimuang; Kousuke Sanada; Kazuo Mori; Hideo Kobayashi (My University, 2016)
This paper proposes a minimum mean square error-frequency domain equalization (MMSE-FDE) method for training sequence inserted orthogonal frequency division multiplexing (TS-OFDM) signal under higher mobile environments. The salient features of proposed method are to enable the acquisition of frequency diversity gain by using an enhanced channel impulse response (CIR) matrix and to enable the reduction of complexity by using a fast algorithm for inverse matrix calculation. From the simulation results, this paper confirms that the proposed MMSE-FDE method can achieve better bit error rate (BER) performance than the conventional MMSE-FDE methods with keeping lower complexity under higher mobile environments.
Keywords: SC-FDE; Transmit diversity; Blind Source Separation Techniques